POLÍTICAS LINGUÍSTICAS PARA UM ENSINO CRÍTICO DE LÍNGUA INGLESA: AÇÕES E CONTRADIÇÕES NA CONTEMPORANEIDADE - Betim, Deleon (2016)
This study aims to investigate if teachers from a language school in the city of Carambeí – PR, notably a multilingual e multicultural place, have propagated hegemonic discourses about English or if, on the other hand, they have problematized them. By hegemonic discourses, we mean the speeches that have been constantly repeated, often, these speeches are presented at relevant places in society, which allow for the goals to be achieved inside their effects and reproduction (PINTO, 2014). Thus, we related our goal to the issues of language politics and language teaching (CORREA, 2014; RAJAGOPALAN, 2014), as we understand that this issue engenders attitudes and behaviors of teachers in the classroom. Thus, we conducted individual interviews with six teachers from the school and a meeting of discussion with three of those interviewed teachers. In the interviews we discussed various topics, not only issues relating to language politics, but also the experiences of participants in teaching and learning languages, and questions about forms of education that intend to be critical. At the meeting, the text written by Kramsch (2012) was the starting point of discussions whose themes were also diverse, especially in the interests of English language teaching and learning. Therefore, we emphasize that our methodology is qualitative, with ethnographic aspects and action research (LÜDKE; ANDRÉ, 1986; TELLES, 2002; TRIPP, 2005). From this view, we can also point out that we are located within the Applied Linguistics. (MOITA LOPES, 2008; PENNYCOOK, 2006). The theoretical apparatus that contributed to this research consisted of (CALVET, 2007; RAJAGOPALAN, 2011; 2013; JORDÃO, 2014, LEFFA, 2011, SIQUEIRA, 2008, LIMA, 2009, et al) to name a few, which brought contributions in different aspects and themes in the issues of language and more specifically the teaching of English. The results indicate that the survey participants have lines that suggest English teaching for a bias usually innovative, but with many caveats and / or inconsistencies, which as a rule, focus on traditional positions within that school. Therefore, we conclude that there are many nebulae issues within the English teaching in the researched context, and by extension, in other teaching-learning contexts, especially about the speeches that we repeat, often in situations of uncertainty. Thus, these discourses fill the doubts about the uncertain and reiterate what is already established. Finally, we hope to have contributed to the foreign language teaching issues, mainly, when we show its relations with cultural issues, whether they are individual and subjective, whether collective, which often are overlooked.